Comparative Study of Methods for Producing Nanoemulsions Using Vegetable Oil as an Excipient: Narrative Review - Ervita Dwi Cahyani; Yandi Syukri; Sulaiman Zubair (International Journal of Health and Pharmaceutical (IJHP), 2025)
Nanoemulsions using vegetable oils as excipients have gained attention for their ability to improve the delivery and stability of bioactive compounds in pharmaceutical and food applications. This study aims to systematically compare various methods for preparing nanoemulsions with vegetable oil excipients. A narrative literature review was conducted, focusing on articles published between 2021 and 2025 from Google Scholar, PubMed, and ScienceDirect. The population comprised all relevant scientific articles, with purposive sampling based on inclusion criteria such as active DOI and accessibility. Data were analyzed qualitatively using content analysis to identify, group, and compare preparation methods, physicochemical characteristics, and product stability. Results indicate that high-energy methods like ultrasonication and high-pressure homogenization produce nanoemulsions with smaller, more uniform droplets and greater stability, while low-energy methods such as spontaneous emulsification are simpler but may yield less stable products. The choice of vegetable oil and surfactant significantly affects droplet size and stability. In conclusion, optimizing both the oil type and preparation method is essential for developing effective nanoemulsion-based products.